Comparison of digital DATCOM and wind tunnel data of a winged hybrid airship’s generic model - Ul Haque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin; Ali, JS Mohamed (2014)
Use of low fidelity tools in designing subscale generic wind tunnel models is usually required to get first-hand knowledge about general trends of aerodynamic and stability parameters. Most of such tools are limited to well-defined conventional aircraft configurations. In the present work, aerodynamic and stability characteristics of a winged hybrid airship is explored at low subsonic speed by using Aircraft Digital DATCOM, which is based on semi-empirical methods for preliminary aircraft geometries. Spheroidal ellipsoidal shaped hull of the airship is modeled in DATCOM along with the geometrical details of wing and empennages. The prediction of zero lift drag coefficient, coefficient of lift and pitching moment is the focus of this paper. Except the drag coefficients, trends of analytical results compare well with experimental data